Financing decisions of firms: the roles of legal systems, shareholder rights and creditor rights - Özer, Gökhan; Çam, İlhan (Wiley, 2021)
We examine how firms finance their investments, dividends, and profit shortfalls in different institutional environments. Using firm-level data from 71 countries, we employ a dynamic multi-equation system addressing the interdependence and intertemporal nature of financing decisions. We find that equity and long-term debt (short-term debt and cash) play a major role in financing capital expenditures (working asset investment). As the institutional environment strengthens, (i) firms increase (decrease) their reliance on equity (debt) issuance in financing capital expenditures, (ii) firms decrease their leverage, and (iii) they extend their debt maturity. We further report several findings on the effects of financial development.
Keywords: Financing decisions; Legal systems; Shareholder rights; Creditor rights; Seemingly unrelated regression